The effect of portable air-purifiers in improving indoor air quality in pediatric intensive care units at two tertiary hospitals in Riyadh, Saudi Arabia - Al-Ghamdi, Waleed Saeed; El-Saed, Aiman; Al-Shamrani, Majid; Al-Rabou, Ali; Neamatallah, Abdullatif; Al-Mehmadi, Fahad (Journal of agricultural, environmental and veterinary sciences, 2023)
Background: A set of environmental preventive measures involving ventilation control within healthcare facilities is well established. Portable air purifiers have been introduced in recent years as one of alternative technologies used to prevent infection and other respiratory complications in indoor environment. Objective: To asses indoor air quality in pediatric intensive care units at two tertiary hospitals in Riyadh, Saudi Arabia in the presence and absence of portable air purifiers.Method: Fine particles (PM 2.5) and coarse particles (PM10) were obtained using optical particle counter and microbial counts were obtained using Andersen air sampler from outdoor and two patient rooms in pediatric intensive care units. Pollutants levels reduction between outdoor and indoor were calculated and compared using Statistical Package for the Social Sciences software (SPSS Version 27.0. Armonk, NY: IBM Corp) were utilized for statistical analysis. Results: In hospital A and B, non-protective environment room (NPE) had a significantly higher number of fine particles and total bacterial count (TBC) respectively than semi-protective environment room (SPE). Meanwhile, there was significantly higher reductions of fine particles (hospital A) and coarse particles, fine particles and TBC (hospital B) in SPE rooms compared with NPE room. Hospital-A had significantly higher reduction efficacy compared with matched rooms in hospital-B for fine particles, coarse particles, and TBC. Conclusion: This study demonstrated that portable air purifiers have a great impact in the reduction of indoor air pollutants in PICUs including fine particulate matters and TBC in particular. Furthermore, ventilation systems equipped with HEPA filters along with portable air purifiers significantly reduce the levels indoor air pollutants of outdoor sources. Moreover, this study showed that newer and well-maintained HVAC systems play a significant role in controlling the levels of airborne pollutants.
Keywords: Air purifiers; Bacterial; Coarse particles; Fungal; Fine particles; High Efficiency Particulate Air